Introgression of the QTL qSB11-1TT conferring sheath blight resistance in rice (Oryza sativa) into an elite variety, UKMRC 2, and evaluation of its backcross-derived plants - Hossain, Md. Kamal; Islam, Mohammad Rafiqul; Sundaram, Raman Meenakshi; Bhuiyan, Md. Atiqur Rahman; Wickneswari, Ratnam (Frontiers in Plant Science, 2023)
Sheath blight (SB) is the most damaging fungal disease in rice caused by a soil-borne pathogenic fungus, Rhizoctonia solani Kuhn (R. solani). The disease resistance in rice is a complex quantitative trait controlled by a few major genes. UKMRC2 is a newly developed elite rice variety that possesses higher yield potentiality but is susceptible to sheath blight disease indicating a huge risk of varietal promotion, mass cultivation, and large-scale adoption. The aim of our present study was the development of varietal resistance against R. solani in UKMRC2 to enhance its stability and durability in a wide range of environments and to validate the effects of an SB-resistance QTL on the new genetic background like UKMRC2 suitable for marker-assisted selection in the future breeding program. However, in our study, we developed 290 BC1F1 backcross progenies from a cross between UKMRC2 and Tetep to introgress the QTL qSBR11-1TT into the UKMRC2 genetic background. Validation of the introgressed QTL region was performed via QTL analysis based on QTL-linked SSR marker genotyping and phenotyping against R. solani artificial field inoculation techniques. The QTL qSBR11-1TT was then authenticated with the results of LOD score (3.25) derived from composite interval mapping, percent phenotypic variance explained (14.6%), and additive effect (1.1) of the QTLs. The QTL region was accurately defined by a pair of flanking markers K39512 and RM7443 with a peak marker RM27360. Thus, the presence of the QTL qSBR11-1TT has been legitimated and confirmed in the URMRC2 genetic background which reveals an opportunity to use the QTL in the future marker-assisted breeding program to boost the sheath blight resistance in rice.